Acute myocarditis associated with desmosomal gene variants. (3rd October 2022) - Ammirati, E; Raimondi, F; Piriou, N; Mohiddin, S A; Imazio, M; Aquaro, G; Olivotto, I; Van De Heyning, C M; Peretto, G; Merlo, M; Klaassen, S; Poller, W; et al.
Abstract: Background: The risk of adverse cardiovascular events in patients with acute myocarditis (AM) and desmosomal gene variants (DGV) remains unknown. Purpose: To ascertain the risk of death, ventricular arrhythmias, recurrent myocarditis, and heart failure (main endpoint) in patients with AM and pathogenic or likely pathogenetic DGV. Methods: In a retrospective international study from 23 hospitals, 97 patients were included: 36 with AM and DGV (DGV(+)), 25 with AM and negative gene testing (DGV(−)), and 36 AM patients without genetics (w/o genetics). All patients had troponin elevation plus findings consistent with AM on histology or at cardiac magnetic resonance imaging (CMRI). In 86 patients CMRI changes in function and structure were re-assessed at follow-up. Results: In the DGV(+) AM group (88.9% DSP variants), median age was 24 years, 91.7% presented with chest pain, and median left ventricular (LV) ejection fraction was 56% on CMRI (p=NS vs. the other 2 groups). Kaplan-Meier curves demonstrated a higher risk of the main endpoint in DGV(+) AM compared to DGV(−) and w/o genetics patients (62.3% vs. 17.5% vs. 5.3% at 5 years respectively; p<0.0001), driven by myocarditis recurrence and ventricular arrhythmias (Figure 1A, B). At follow-up CMRI, a higher number of late-gadolinium enhanced segments was found in DGV(+) AM. Conclusions: Patients with AM and evidence of DGV have a higher incidence of adverse cardiovascular events compared with AM patients without DGV. Further prospective studies are needed to ascertain if genetic testing might improve risk stratification of patients with AM who are considered at low risk. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Italian Ministry of Health